Hebrews’ High Priestly Christology: Models, Method and Aim - Regev, Eyal (Religions, 2021)
This article suggests a systematic analysis of the ways the author of the Letter to the Hebrews links Christ and the sacrificial system, exploring the author’s method of using the sacrificial system in his Christology. It points to the issues in which Hebrews embraces traditional Jewish cultic ideas and—building on these basics—those in which Hebrews greatly diverges and modifies high priestly features. The manner in which the author bases his Christology on the sacrificial cult shows that he acknowledges the efficacy of the high priest and sacrifices for contending with sin. Even when modifying the priestly cult to show that Christ’s atonement is superior to, and takes the place of, the Temple cult, he bases himself on the fundamentals of the high priest entering the Holy of Holies with blood. He uses the sacrificial cult as a model for Christology, like a map for navigating Christ’s doctrine of salvation. It is suggested that Hebrews’ aim is to make sense of Jesus’ death and atonement, perhaps even to shed light on Pauline Christological and cultic metaphors.